Duodenal Perforation Simulating as Duodenal Duplication Cyst in a Neonate: A Case Report - Jayalaxmi Shripati Aihole; Narendra Babu (EL-Med-Pub, 2019)
Spontaneous duodenal perforation in neonates (SDPN) is a rare surgical emergency. Only few cases have been reported. A neonate presented with abdominal distension investigated with imaging modalities which gave suspicion of a duodenal duplication or choledochal cyst. At surgery, a duodenal perforation with local collection, was encountered simulating a duodenal duplication cyst.